Synchronization of synchronized springboard divers in different age groups - Naundorf, F.; Wenzel, K.; Krug, J. (ISBS - Conference Proceedings Archive (Konstanz), 2008)
Investigation of age-related development of sport performance is an important task to reach best performance in elite sport age. Especially in synchronized diving there is the problem of how to develop different parts of performance (difficulty, movement quality and synchronization). Synchronization is measurable with criteria such as spatial synchronization and synchronization in timing. Our research in different age groups in Germany shows an increase in difficulty and quality of water entry from talent divers to elite divers. But for spatial synchronization and synchronization in timing there is no difference between the age groups. Young divers are as good as elite divers in synchronization but their dives are not so difficult. If you look at synchronized judges values, these findings can not be confirmed.